Nationwide outcomes in patients undergoing surgical exploration without resection for pancreatic cancer. Issue 11 (22nd August 2017) - van der Geest, L. G. M.; Lemmens, V. E. P. P.; de Hingh, I. H. J. T.; van Laarhoven, C. J. H. M.; Bollen, T. L.; Nio, C. Y.; van Eijck, C. H. J.; Busch, O. R. C.; Besselink, M. G.; ,
Abstract: Background: Despite improvements in diagnostic imaging and staging, unresectable pancreatic cancer is still encountered during surgical exploration with curative intent. This nationwide study investigated outcomes in patients with unresectable pancreatic cancer found during surgical exploration. Methods: All patients diagnosed with primary pancreatic (adeno)carcinoma (2009–2013) in the Netherlands Cancer Registry were included. Predictors of unresectability, 30‐day mortality and poor survival were evaluated using logistic and Cox proportional hazards regression analysis. Results: There were 10 595 patients with pancreatic cancer during the study interval. The proportion of patients undergoing surgical exploration increased from 19·9 to 27·0 per cent ( P < 0·001). Among 2356 patients who underwent surgical exploration, the proportion of patients with tumour resection increased from 61·6 per cent in 2009 to 71·3 per cent in 2013 ( P < 0·001), whereas the contribution of M1 disease (18·5 per cent overall) remained stable. Patients who had exploration only had an increased 30‐day mortality rate compared with those who underwent tumour resection (7·8 versus 3·8 per cent; P < 0·001). In the non‐resected group, among those with M0 (383 patients) and M1 (435) disease at surgical exploration, the 30‐day mortality rate was 4·7 and 10·6 per cent ( P = 0·002), median survival was 7·2 and 4·4 months ( P < 0·001), and 1‐year survival rates were 28·0 and 12·9 per cent, respectively. Among other factors, low hospital volume (0–20 resections per year) was an independent predictor for not undergoing tumour resection, but also for 30‐day mortality and poor survival among patients without tumour resection. Conclusion: Exploration and resection rates increased, but one‐third of patients who had surgical exploration for pancreatic cancer did not undergo resection. Non‐resectional surgery doubled the 30‐day mortality rate compared with that in patients undergoing tumour resection. Abstract : Negative impacts